Hydroxynorketamines: Pharmacology and Potential Therapeutic Applications - Highland, Jaclyn N.; Zanos, Panos; Riggs, Lace M.; Georgiou, Polymnia; Clark, Sarah M.; Morris, Patrick J.; Moaddel, Ruin; Thomas, Craig J.; Zarate, Carlos A.; Pereira, Edna F.R.; Gould, Todd D. (Pharmacological reviews, 2021)
Hydroxynorketamines (HNKs) are formed in vivo after (R,S)-ketamine (ketamine) administration. The 12 HNK stereoisomers are distinguished by the position of cyclohexyl ring hydroxylation (at the 4, 5, or 6 position) and their unique stereochemistry at two stereocenters. Although HNKs were initially classified as inactive metabolites because of their lack of anesthetic effects, more recent studies have begun to reveal their biologic activities. In particular, (2R,6R)- and (2S6)-HNK exert antidepressant-relevant behavioral and physiologic effects in preclinical models, which led to a rapid increase in studies seeking to clarify the mechanisms by which HNKs exert their pharmacological effects. To date, the majority of HNK research has focused on the actions of (2R,6R)-HNK because of its robust behavioral actions in tests of antidepressant effectiveness and its limited adverse effects. This review describes HNK pharmacokinetics and pharmacodynamics, as well as the putative cellular, molecular, and synaptic mechanisms thought to underlie their behavioral effects, both following their metabolism from ketamine and after direct administration in preclinical studies. Converging preclinical evidence indicates that HNKs modulate glutamatergic neurotransmission and downstream signaling pathways in several brain regions, including the hippocampus and prefrontal cortex. Effects on other neurotransmitter systems, as well as possible effects on neurotrophic and inflammatory processes, and energy metabolism, are also discussed. Additionally, the behavioral effects of HNKs and possible therapeutic applications are described, including the treatment of unipolar and bipolar depression, post-traumatic stress disorder, chronic pain, neuroinflammation, and other anti-inflammatory and analgesic uses. Preclinical studies indicate that hydroxynorketamines (HNKs) exert antidepressant-relevant behavioral actions and may also have analgesic, anti-inflammatory, and other physiological effects that are relevant for the treatment of a variety of human diseases. This review details the pharmacokinetics and pharmacodynamics of the HNKs, as well as their behavioral actions, putative mechanisms of action, and potential therapeutic applications.